1998
DOI: 10.1177/096100069803000406
|View full text |Cite
|
Sign up to set email alerts
|

A sociological study of public library use in Ankara, Turkey

Abstract: Reports results of a sociological and demographic study of public library users in Ankara, Turkey, in order to determine the level of public use and to isolate the factors affecting this usage. A thorough survey of the history and statistics of Turkish public libraries is followed by the results of the user survey, employing the society survey method, involving 1800 users (aged six years and over) in three socioeconomic stratas. The study took usage of the library as the dependent variable and demographic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…En un ejercicio de comparación de los resultados de este estudio con los de otros vistos en la revisión bibliográfica, cabe destacar que las variables del entorno socioeconómico que se han considerado en el análisis por regiones (Educación, PIB, Desempleo), no resultaron tampoco predictores con significancia en algunos de ellos (Yilmaz, 1998 . Pese a ello, son muchos los estudios en que dichas variables sí que resultaron significantes en relación al uso de las bibliotecas (Creaser y Sumsion, 1995;Yilmaz, 1998;Smith, 1999;Japzon y Gong, 2005;Uddin y otros, 2006;Burke, 2007;Sei-Ching y Kyung-Sun, 2008;Lara y otros, 2015). A su vez, en nuestro estudio las variables referidas al PIB y Educación no resultaron predictores, mientras que en algunos de los revisados sí que se encontró relación significativa y negativa con los préstamos (Huysmans y Hillebrink, 2008).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En un ejercicio de comparación de los resultados de este estudio con los de otros vistos en la revisión bibliográfica, cabe destacar que las variables del entorno socioeconómico que se han considerado en el análisis por regiones (Educación, PIB, Desempleo), no resultaron tampoco predictores con significancia en algunos de ellos (Yilmaz, 1998 . Pese a ello, son muchos los estudios en que dichas variables sí que resultaron significantes en relación al uso de las bibliotecas (Creaser y Sumsion, 1995;Yilmaz, 1998;Smith, 1999;Japzon y Gong, 2005;Uddin y otros, 2006;Burke, 2007;Sei-Ching y Kyung-Sun, 2008;Lara y otros, 2015). A su vez, en nuestro estudio las variables referidas al PIB y Educación no resultaron predictores, mientras que en algunos de los revisados sí que se encontró relación significativa y negativa con los préstamos (Huysmans y Hillebrink, 2008).…”
Section: Discussionunclassified
“…La situación es diferente si se atiende a la investigación en el ámbito internacional. La relación entre variables geográficas, económicas, demográficas y socioeconómicas del tipo edad, género, estado civil, nivel de educación, ocupación, o nivel de ingresos, y variables referidas al uso de bibliotecas públicas, aparece como tema central en diversos trabajos y a lo largo del tiempo (Sanderson, 1950;Obokoh y Arokoyu, 1991;Yilmaz, 1998;Japzon y Gong, 2005;Koontz y otros, 2005;Uddin y otros, 2006;Burke, 2007;Keshvari y otros, 2015;Chen y otros, 2016).…”
Section: Revisión Bibliográficaunclassified
“…Several studies on public libraries in Turkey have been published in both national and international literature (Keseroğlu, 1989; Sağlamtunç, 1995; Yalvac, 2004; Yılmaz, 1998, 2008, 2010). In these studies, findings about the role of the public libraries in Turkey have been presented in the form of various statistical data.…”
Section: Research On Public Libraries In Turkeymentioning
confidence: 99%
“…Yılmaz (2008) summarized the history and current status of "Public Libraries in Turkey" from the dawn of civilization to the present. In an earlier study, Yılmaz surveyed 1800 public library users in Ankara, Turkey and concluded the community was "not using the public library enough" (Yılmaz 1998 Groves (2007). Throughout this literature, there is scant focus on collection development.…”
Section: Literature Reviewmentioning
confidence: 99%